Expanding a 3D Solid Reconstruction System using Two Views to the System using Three Views - Hoang, Long (Old Journal, 2018)
The Solid 3D model is essential in mechanical engineering because of its applications in the areas of CAD/CAM/CAE/CAQ. A trend to create this model, that has long been studied by scientists around the world, is 3D model reconstruction from views. With this method, it is easy to enter geometric information as well as can use 2D drawings that have already existed. Our previous works have solved the problem of automatic reconstruction from two views for the usual details. Expanding this method, in this paper, the author proposed a method of reconstruction from three views for the more complex details. That method has been installed and tested by an ADSRX program running on AutoCAD software.